Analysis of ecstasy in human urine using by high performance liquid chromatography - Monlinong, Jason Paul C.; Portilla, Ma. Cristina B.; Reyes Gian Carlo P.; Pascual, Cherrie B. (2011)
Ecstasy or n-methyl-3, 4-methylenedioxymethamphetamine (MDMA) is one of the most popular club drugs. This drug was inenvted to treat obesity but is currently placed under Schedule 1 of controlled substances, It is a psychoactive drug like methamphetamine or shabu. Ecstasy in urine was analysed using high performance liquid chromatography (HPLC) with UV detection set at 254 nm. Chromatographic analysis was carried out with a Luna 5u C18 revered phase column and (87:5:5:3) water:methanol:acetonitrile:ammonium buffer as mobile phase at flow rate of 0.5mL/min. Ephedrine was used as an integral standard. MDM and ephedrine showed average retention times of ~2.5 min and ~2.8 min respectively. Analysis of 0.50 ppm MDMA had % coefficient of variation (%CV) of 0.57% for the retention time of MDMA and 6.6% for peak area. Inter day analysis showed %CV of 2.2% for retention time and 3.68% for peak area. Linear response was obtained over the concentration range of 0.10 ppm-1.00 ppm. The limit of detection (LOD) was 0.03 ppm. Different concentrations of MDMA were spiked in certified drug-free urine and a linear response at the same concentration range after liquid-liquid extraction with ether was also obtained. Gradient elution using (87:5:5:3) water:methanol:acetonitrile:ammonium buffer as mobile phase B was employed to imrpove standard separation of MDMA from ephedrine on urine matrix. Different spiked urine samples underwent the same extraction procedure with ether and recoveries ranged from 81-104%. HPLC analysis of ecstasy could provide an alternative rapid method to detect this drug of abuse in human urine samlpes.
Keywords: Ecstasy; Urine; High performance liquid chromatography